Publication trends in Counselling and Artificial Intelligence: A Bibliometric Analysis - Hadi, Musthofa; Utami, Rachma Bhakti; Palupi, Ratnaning; Nikmah, Farika; Santoso, Eko Boedi (Jurnal Kajian Bimbingan dan Konseling, 2025)
Current developments in counseling show significant improvements, especially with the increasingly deeper integration of artificial intelligence (AI). This research focuses on analyzing research development trends in counseling and artificial intelligence, with data collected from Scopus-indexed publications from the beginning of 1982 to 2024. From this period, 470 relevant articles were identified for further analysis. The analysis process is carried out using bibliometric methods with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, with the help of R-Biblioshiny software, which allows in-depth analysis of patterns and trends in the literature. The analysis results show that this topic has experienced a significant increase in articles published, with an average annual growth of 11.59%. In addition, this topic also shows a reasonably high citation rate, with an average of 10.81 citations per article, indicating substantial influence in the academic community. Despite this, some areas are still not fully explored, such as artificial intelligence's role in decision-making in counseling, which represents a new and exciting niche for further research. Hopefully, this research will provide additional insights and encourage further research exploring the full potential of integrating artificial intelligence in counseling.